Oncological and prognostic analysis of soft tissue sarcoma of the elbow: report using the bone and soft tissue tumor registry in Japan. (29th July 2021) - Emori, Makoto; Iba, Kousuke; Murahashi, Yasutaka; Shimizu, Junya; Sonoda, Tomoko; Wada, Takuro; Yamashita, Toshihiko; Kawai, Akira
Abstract: Objective: Soft tissue sarcomas in the elbow are extremely rare, and they have primarily been described in case series. Definitive concerning the prevalence and prognostic factors of elbow soft tissue sarcomas remain unknown. We examined the outcome of patients with elbow soft tissue sarcomas and identified the relevant prognostic factors. Methods: In total, 219 patients with elbow soft tissue sarcomas were identified using data from the bone and soft tissue tumor registry in Japan. Differences in demographics, disease characteristics, treatment and survival were compared among the patients. Survival analyses including local recurrence-free survival, distant metastasis-free survival, and overall survival were performed using the Kaplan–Meier method with log-rank tests and the Cox proportional hazards model. Results: Two hundred nineteen patients with elbow soft tissue sarcomas were identified, including 119 males (54.3%) and 100 females (45.7%). In total, 189 patients (86.3%) underwent surgery including re-excision. Of the surgically treated patients, 180 (95.2%) underwent limb salvage surgery, and nine patients (4.8%) underwent amputation. The 5-year overall survival, local recurrence-free survival, and distant metastasis-free survival rates for the entire patient cohort were 76.3, 70.1, and 69.3%, respectively. After adjusting for clinically relevant factors, overall survival was significantly worse among patients with tumors: >10 cm (hazard ratio = 4.34; 95% confidence interval = 1.03–18.2) and metastatic disease (hazard ratio = 6.94; 95% confidence interval = 1.55–31.0). Conclusions: Tumor size was identified as an independent risk factor for poor prognosis. Abstract : The oncological outcome and risk factors of elbow soft tissue sarcomas was investigated. In our series of 219 patients with elbow soft tissue sarcomas, smaller tumors may predict better survival.Level of evidence: Level III; Case-control study; Prognosis Study.